PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN PENGHARGAAN SEBAGAI VARIABEL MODERASI - Sarah Meilin Ginting; Valentine Siagian (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
This research was conducted at PT. Hotma Guna which is engaged in services as a provider of production workforce, office administration, drivers, cleaning personnel, logistics, and lawn mowing. This study aims to determine the effect of the work environment on performance and also we include rewards as a moderating variable. This research uses quantitative research. In this study, researchers used primary data obtained from distributing questionnaires to employees at PT. Hotma Guna, resulting 89 respondents. The results of this study indicate that work environment variables have a significant effect on employee performance variables. This is supported by a significant result of 0.000 and the result of t count> t table which is equal to 6.880> 1.988. In this study, we also found that the reward variable did not strengthen the effect of work environment towards the employee performance. This is supported by a significant result of 0.227 and the value of t count <t table which is equal to -1.216 <1.988.